Stimulus aspects of aversive controls: the retention of conditioned suppression - Hoffman, Howard S. (1963)
Three years ago a tone ending in unavoidable electrical shock was periodically presented to pigeons while they pecked a key for food. When pecking was disrupted by tone, shock was disconnected and the training tone as well as tones of different frequencies were presented. At first, all tones caused a reduction in the rate of pecking, but as testing proceeded, suppression began to extinguish and the gradient narrowed. In the present work, testing was resumed after a 2½-yr interruption. Analysis of the gradients obtained just before and just after the interruption yielded no evidence of changes with the passage of time. As testing proceeded, however, extinction of suppression continued and the gradient all but disappeared. In subsequent experiments with these subjects (Ss) it was found that the presentation of free shocks caused a reappearance of the gradient and that this effect persisted in reduced amount for several sessions after the shock condition was terminated.